Six Sigma methodology application in the evaluation of the glucose results (2014-2016) obtained by the participant laboratories of Programa Nacional de Avaliação Externa da Qualidade (PNAEQ) - Reguengos, João (2018)
Glucose quantification plays a key role in the Diabetes diagnosis and treatment monitoring. In Portugal diabetes prevalence is increasing and last estimates provide a prevalence of 9,8%(1). The main objective of this study was to evaluate the Sigma level of the participant laboratories of the Clinical Chemistry program of PNAEQ (2014-2016) regarding the Glucose quantification, through two different approaches: by applying a linear regression model which enables performance evaluation of each laboratory individually over time(2); and by evaluating the general performance of all laboratories on each sample.